2016
DOI: 10.1159/000446364
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Local Recurrence of Large, Flat Colorectal Polyps after Endoscopic Mucosal Resection

Abstract: Aims: Removal of large, flat colorectal polyps by endoscopic mucosal resection (EMR) is effective, but local recurrences occur regularly. This study investigated risk factors for local recurrence. Method: Cases of EMR of flat colorectal polyps ≥20 mm at an academic center from 2004 to 2011 were retrospectively analyzed for polyp features, resection technique, complications and local recurrences. Behavioral risk factors were retrospectively determined by self-administered questionnaires. Results: Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
1
17
0
4
Order By: Relevance
“…It was reported previously that the rate of recurrence is extremely high (23.8-37.0%) after piecemeal EMR for large lesions [25,26], which is similar to the outcomes of colorectal ESD [27]. ESD is certainly required for large-sized tumors from the perspective of curable treatment, but safety issues should be addressed.…”
Section: Discussionmentioning
confidence: 53%
“…It was reported previously that the rate of recurrence is extremely high (23.8-37.0%) after piecemeal EMR for large lesions [25,26], which is similar to the outcomes of colorectal ESD [27]. ESD is certainly required for large-sized tumors from the perspective of curable treatment, but safety issues should be addressed.…”
Section: Discussionmentioning
confidence: 53%
“…This study demonstrated that the local colon adenoma recurrence rate in our cohort of patients with ≥ 20-mm colon LSTs managed using cap-fitted colonoscopy with EMR and ablation of the resection edge with APC was low (4.5 %). This adenoma recurrence rate was much lower than 16.0 % to 32 % reported in the literature on traditional EMR for non-pedunculated polyps (▶ Table 3) [3,10,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, EMR is regarded as a potential curative procedure which can replace surgery in most cases (16) . It is important, however, to bear in mind that EMR is associated with a non-neglectable risk of recurrent disease, a risk that seems to be higher if piecemeal EMR is performed (17) .…”
Section: Discussionmentioning
confidence: 99%